TV Star - Rachel Renée Russell
Dork Diaries: TV Star authored by Rachel Renee Russell is the seventh book in the series. This series revolves around Nikki Maxwell and her adventures in middle school. Summary Of The Book Nikki Maxwell and her friends are about to get a taste of fame. A reality TV crew is busy following them around and they are here to stay for almost a month as they record their hit song. But now that the cameras are everywhere, and it is creating unexpected problems for Nikki. Is life in the spotlight going to be all about fun and glamor or is it going be a Dork Disaster? The book is packed with packed with Nikki's doodles and diary entries and will make for a fun read for children in the age group of 8 and 12 years. About Rachel Renee Russell Rachel Renee Russell is a renowned author from the US. Apart from this book, Russell has written a number of other books, and they include Dork Diaries: How To Dork Your Diary and Dork Diaries: Tales From A Not-So-Graceful Ice Princess. Rachel Renee Russell is from Saint Joseph, Michigan, and wrote her first books while she was studying in the 6th grade. She is the eldest child in her family, and has two younger sisters and two younger twin brothers. The Dork Diaries written by Russell have more than 10 million copies in print in the US, and have been translated in more than 32 languages. Apart from writing books, Russell also works as an attorney.